Preference and aspiration of youth towards sustainable recreational parks in a city - Mansor, Mazlina; Harun, Nor Zalina (2019)
Daily activities of youth in the digital age, particularly in a city, are revolved around the use of information technology. Youth as young people between the age of 15 and 24 years (The United Nations). The age group of youth in Malaysia are between 18 and 25 years if based on development programmes and activities (MOYS, 1997). Excessive time in information age such as immersing in social media resulted in sedentary activities of the youth. Lesser time is spent on outdoor activities during leisure-time. Health statistics in Malaysia has shown that non-communicable diseases (NCDs), e.g. obesity and diabetes do not only affect adults but young people and adolescents alike. Thus, engaging in physical outdoor activities is important, especially when youth can have contact with natural landscape. Nature in a city is formed by recreational parks and green spaces in different sizes. Nature is proven by many researches to offer various health benefits physically, mentally and socially. As such, recreational parks in a city act as the reinforcement to promote a healthy lifestyle for youth’s wellbeing. To attract youth to utilize recreational parks in a city, their reasons to spend leisure-time in recreational parks must be examined. Designing based on youth’s preference and aspiration could promote and attract them to utilise the recreational parks. The ‘nature’ should provide more than simply basic facilities to ensure its sustainability of use in the future. The paper explores preference and aspiration of parks that youth needs as factors that attracts them to the recreational spaces, through questionnaire survey (n≈1000) regarding recreational parks in Kuala Lumpur and Putrajaya. SPSS findings of descriptive statistics suggest that youth prefers to visit the recreational parks because of natural attributes, emotional well-being and socialising opportunities. Other factors that they aspire are specialised activities (organisational programmes, designated play spaces) and functional facilities (up-to-date play facilities, maintenance). These factors provide a basis to assist future planning of parks in a city specifically for youth organisations, ministry of youth and sport, practitioners and city authorities, because a healthy youth, body and mind is a valuable human capital for nation building.